Potential of PALBI‐T score as a prognostic model for hepatocellular carcinoma in alcoholic liver disease. Issue 1 (5th January 2022) - Tanaka, Kazunari; Tsuji, Kunihiko; Matsui, Takeshi; Kang, Jong‐Hon; Sakurai, Yasuo; Kodama, Yoshihisa; Minami, Ryosuke; Watanabe, Kiichi; Katanuma, Akio
Abstract: Background and Aim: With the control of viral hepatitis, alcoholic hepatocellular carcinoma (HCC) is becoming increasingly important in Japan. In alcoholic cirrhosis, the impact of portal hypertension is significant. Thus, it may be difficult to predict prognosis accurately with the reported prognostic scores. Here we propose the platelet‐albumin‐bilirubin tumor nodes metastasis (TNM) score (PALBI‐T score) as a prognostic model for HCC in alcoholic liver disease, and investigate its usefulness. The PALBI‐T score is an integrated score based on the TNM stage and PALBI grade including platelets, reflecting portal hypertension. Methods: This study included 163 patients with alcoholic HCC treated at our Center from 1997 to 2018. We compared the prognostic prediction abilities of the Japan Integrated Staging (JIS) score, ALBI‐T score, and PALBI‐T score. The PALBI‐T score was calculated similarly to the JIS and ALBI‐T scores. Areas under the receiver operating characteristic curve (AUC) were calculated for predicting overall survival (OS). Results: In predicting the 1‐year survival, the JIS score had a larger AUC (AUC = 0.925) than the ALBI‐T score (AUC = 0.895) and PALBI‐T score (AUC = 0.891). On the other hand, there was no significant difference in predicting OS among the integrated scores. The PALBI‐T score (AUC = 0.740) had the largest AUC, and the JIS score (AUC = 0.729) and ALBI‐T score (AUC = 0.717) were not significantly different from the PALBI grade (AUC = 0.634). The PALBI grade reflected the degree of portal hypertension. Conclusion: In patients with alcoholic HCC, the Japan Integrated Staging score is useful for predicting short‐term prognosis. The PALBI‐T score, which reflects portal hypertension, appears to be a more valid prognostic score for predicting long‐term prognosis. Abstract : In this study, we propose the platelet‐albumin‐bilirubin tumor nodes metastasis score (PALBI‐T score) as a prognostic model for hepatocellular carcinoma (HCC) in alcoholic liver disease, and investigate its usefulness. We compared the prognostic prediction abilities of the Japan Integrated Staging (JIS) score, ALBI‐T score, and PALBI‐T score. Although, in patients with alcoholic HCC, the JIS score is useful for predicting short‐term prognosis, the PALBI‐T score, which reflects portal hypertension, appears to be a more valid prognostic score for predicting long‐term prognosis.